Modulation of viscoelasticity and interfacial potential of polyelectrolyte brush by Ion-specific interactions - Yamamoto, Akihisa; Hayashi, Kentaro; Sumiya, Ai; Weissenfeld, Felix; Hinatsu, Satoko; Abuillan, Wasim; Nakahata, Masaki; Tanaka, Motomu (Frontiers in Soft Matter, 2022)
Polyelectrolyte brushes have drawn increasing attention because their physicochemical properties can be modulated by adjustment of the pH and ion concentration. Here, we report the controlled grafting of poly acrylic acid containing cysteine side chains onto supported lipid membranes to allow for the modulation of viscoelasticity as well as interfacial potential by ion-specific interactions, that is, with cadmium ions. Quartz crystal microbalance with dissipation indicated that the resonance frequency increased and the dissipation decreased as the cadmium concentration increased, attributed to the dehydration of brushes. Systematic variation of the molecular structure demonstrated that the coexistence of thiol and carboxyl moieties is necessary for the viscoelastic response, suggesting that these structural features, common with naturally occurring proteins, form complexes with cadmium ions. Analysis of the height fluctuation of colloidal particles by reflection interference contrast microscopy indicated that the change in the viscoelasticity of the polymer brush layer alters the curvature of the effective interfacial potential. Intriguingly, we found that modulation of the viscoelasticity and interfacial potential caused by calcium ions is weak, suggesting that the interaction is ion-specific. Polymer brushes that can alter the interfacial potential through changes in the degree of hydration opens new avenues for the design of smart, adaptable surfaces.